WOMEN EMPOWERMENT THROUGH RURAL LIVELIHOOD MISSION: REFLECTIONS FROM TRIPURA (CAHIERS MAGELLANES-NS, 2024)
The government of India has celebrated the year 2001 as the year of Women Empowerment. It introduced various schemes to provide financial supports to Self Help Groups (SHG) members. The paper examines the effectiveness of SHGs formed under Tripura Rural Livelihood Mission (TRLM) in empowering rural women in Tripura. Primary data have been collected through structured and semi structured questionnaire from 100 members of SHGs, 25 each from four selected rural development blocks under Gomati, South Tripura, West Tripura and Dhalai District. The paper reveals that TRLM has helped women to grow a feeling of greater extrinsic control but it has not been effective enough to develop intrinsic capacity of women with greater self-confidence enabling women external barriers and bringing a change in traditional ideology and existing social norms which are largely drawn on biological determination.